PREPARATION OF ACCOUNTING SYSTEM IN JEWEL JOURNEY AUTO WASH - Kennardi Tanujaya; Reny Reny (ConCEPt - Conference on Community Engagement Project, 2022)
This social dedication aims to create an accounting record system for Jewel Journey Auto Wash or JJ Auto Wash that can be implemented in business operations. JJ Auto Wash is a service business that has been running for 1.5 years. Based on the information obtained, JJ Auto Wash has problems in the recording system and the preparation of business financial reports. Instead of accounting recording system JJ Auto Wash still uses manual method to record transaction occured in a notebook. The method that will be applied in this research is the waterfall method which begins with analyzing, designing the system, testing and implementing the system. The result of this study is an accounting record system developed using Microsoft Access which can record and print financial reports for a certain period for JJ Auto Wash. Hopefully JJ Auto Wash will keep using this recording system, in order to produce better financial reports. Hopefully in the future, the dedication is able to engaged more sectors such as trade dan manufacturing.